Claiming credit and avoiding blame: political accountability in Greek and Turkish responses to the COVID-19 crisis - Zahariadis, Nikolaos; Petridou, Evangelia; Oztig, Lacin Idil (WILEY, 2020)
Using a framework developed by Hood and adapting it to crises, we explore the factors behind the use of three types of political accountability strategies- presentational, policy, and agency-during responses to the COVID-19 crisis in Greece and Turkey. We situate the comparison in the current political context and conclude with implications for political survival as leaders attempt to balance public accountability, political expediency, and national health.
Keywords: accountability; blame avoidance; COVID-19 crisis; credit claiming; Greece; Turkey; TRANSPARENCY; Government & Law; Public Administration